2015
DOI: 10.1371/journal.pone.0142351
|View full text |Cite
|
Sign up to set email alerts
|

How Much Do Metamemory Beliefs Contribute to the Font-Size Effect in Judgments of Learning?

Abstract: Evidence shows that the font size of study items significantly influences judgments of learning (JOLs) and that people’s JOLs are generally higher for larger words than for smaller words. Previous studies have suggested that font size influences JOLs in a belief-based way. However, few studies have directly examined how much people’s beliefs contribute to the font-size effect in JOLs. This study investigated the degree to which font size influenced JOLs in a belief-based way. In Experiment 1, one group of part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(81 citation statements)
references
References 22 publications
4
76
1
Order By: Relevance
“…6). Furthermore, ample evidence indicates that other beliefs that people have about memory impact their JOLs (e.g., Hu et al, 2015;Jia et al, 2016;Mueller & Dunlosky, 2017;Mueller et al, 2016;Mueller et al, 2014;Mueller et al, 2013;Susser, Jin, & Mulligan, 2016;Witherby & Tauber, 2017). Additional evidence of the influence of people's beliefs comes from research about memory self-efficacy, which pertains to people's beliefs about how well they can remember information (e.g., Hertzog, Dixon, & Hultsch, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6). Furthermore, ample evidence indicates that other beliefs that people have about memory impact their JOLs (e.g., Hu et al, 2015;Jia et al, 2016;Mueller & Dunlosky, 2017;Mueller et al, 2016;Mueller et al, 2014;Mueller et al, 2013;Susser, Jin, & Mulligan, 2016;Witherby & Tauber, 2017). Additional evidence of the influence of people's beliefs comes from research about memory self-efficacy, which pertains to people's beliefs about how well they can remember information (e.g., Hertzog, Dixon, & Hultsch, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has established that people's beliefs about the impact of a cue can influence their JOLs (e.g., Hu et al, 2015;Jia et al, 2016;Mueller & Dunlosky, 2017;Mueller, Dunlosky, & Tauber, 2016;Mueller, Dunlosky, Tauber, & Rhodes, 2014;Mueller, Tauber, & Dunlosky, 2013;Susser, Jin, & Mulligan, 2016;Undorf & Zimdahl, 2019;Witherby & Tauber, 2017). One way that this contribution of memory beliefs has been evaluated is with questionnaires probing for people's beliefs about their memory (Besken, 2016;Jia et al, 2016;Koriat, Bjork, Sheffer, & Bar, 2004;Kornell, Rhodes, Castel, & Tauber, 2011;Li et al, 2017;Mueller et al, 2016;Mueller, Dunlosky, Tauber, & Rhodes, 2014;Mueller et al, 2013;Price, McElroy, & Martin, 2016;Witherby & Tauber, 2017, 2018.…”
Section: Contribution Of Beliefs To Judgments Of Learningmentioning
confidence: 99%
“…Although metamemory monitoring has been extensively explored for over 50 years (Hart, 1965), the underlying causal mechanisms are still unclear. There is substantial evidence that people's beliefs affect their JOLs (Hu et al, 2015;Mueller & Dunlosky, 2017;Mueller, Dunlosky, Tauber, & Rhodes, 2014). Hu et al (2015), for instance, found that people hold a priori beliefs that large words are more memorable than small words and they incorporate these beliefs into the judgment process.…”
Section: Theories Of Metamemory Monitoringmentioning
confidence: 99%
“…Nonetheless, recent research has revealed that a range of factors may bias people's metamemory monitoring. For instance, although the font size of study words has no effect on later recall, people give higher judgments of learning (JOLs; i.e., the judged likelihood that a given item will be remembered at a later test) to large-than to small-font-size words (Hu et al, 2015;Hu, Liu, Li, & Luo, 2016;Rhodes & Castel, 2008;Yang, Huang, & Shanks, 2017). Along the same lines, although loudness has no effect on memory retention, people give higher JOLs to loud than to quiet words (Rhodes & Castel, 2009).…”
mentioning
confidence: 99%
“…When compared between types of multiple-choice questions and essays, psychology students prefer exams with essay type questions rather than multiple-choice questions [20]. However, the characteristics of other students can be very different because each department or program of study has a different learning tendency pattern that greatly impacts the preferred pattern of choice of questions.…”
Section: Advances In Social Science Education and Humanities Researcmentioning
confidence: 99%